Pengaruh Ketebalan Inner-Helical Fin Terhadap Charcteristic of Performance pada Head Exchanger - Usman, Ishak; Wahyudi, Slamet; Argo, Bambang Dwi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2010)
Effect of inner-helical fin on the rate of heat transfer and flow friction factor in a double pipe heat exchanger (double tube heat exchanger) to make a split and disrupt the flow pattern of a streamlined flow of the fluid flowing in the pipe section in the (inner tube) that cause turbulence (molecule-molecule level of randomness good fluid) that can increase the heat transfer rate in the the pipe . Inner-helical fin has a varied thickness of 1 mm, 22 mm and 3 mm are mounted on the pipe where the inside diameter of the inner-helical fin attached to the wall in the inner pipe. Hot water discharge on the inner pipe ditelitil ranging from 400 to 900 liters / h with interval increase in 100 liter / hour and the volumetric flow rate of cold water on the outer tube (outertube) is kept constant 900 liters / hour. The test results of each inner-helical fin thickness compared with the test results without the inner-helical fin (plain tube) and obtained the overall heat transfer rate has increased 60 to 65% of the plain tube, heat exchanger effectiveness of58.56 to 63, 64% and friction factor of 63.13 to 63.51 of the plain tube.Keywords : Inner-helical fin, Heat exchanger, rate of heat transfer, friction factor